BASP1 labels neural stem cells in the neurogenic niches of mammalian brain - Louis N. Manganas (Nature Portfolio, 2021)
Abstract The mechanisms responsible for determining neural stem cell fate are numerous and complex. To begin to identify the specific components involved in these processes, we generated several mouse neural stem cell (NSC) antibodies against cultured mouse embryonic neurospheres. Our immunohistochemical data showed that the NSC-6 antibody recognized NSCs in the developing and postnatal murine brains as well as in human brain organoids. Mass spectrometry revealed the identity of the NSC-6 epitope as brain abundant, membrane-attached signal protein 1 (BASP1), a signaling protein that plays a key role in neurite outgrowth and plasticity. Western blot analysis using the NSC-6 antibody demonstrated multiple BASP1 isoforms with varying degrees of expression and correlating with distinct developmental stages. Herein, we describe the expression of BASP1 in NSCs in the developing and postnatal mammalian brains and human brain organoids, and demonstrate that the NSC-6 antibody may be a useful marker of these cells.